Status of Divine Word Colleges in Region 1, Philippines - Callanta-Fontanilla, Maria Veronica (Journal of Education and Vocational Research, 2013)
This study aimed to determine the status of Divine Word Colleges in Region I, Philippines, with the use of a self-devised questionnaire. Majority are 31 – 40 years old, females, married, Bachelor’s degree holders with units in the Master’s program, ranked instructor I-IV with 1-10 years of working experience and with monthly salary of Php. 9,001-12,000. Majority of the students are taking up Nursing, aged 19-22 years and females. In terms of the status of the colleges along ten dimensions, an overall descriptive rating of ‘high’ was achieved. There is a significant difference existing between the colleges with eight variables except instruction and library. A relationship exists between civil status and the variables among the administrators, and between highest educational attainment of the respondents and faculty. On the other hand, a negligible and direct perfect degree of relationship was obtained along monthly salary and non-teaching staff variables.